Desain dan analisis pengaruh variasi nilai beban dan kecepatan laju kendaraan terhadap suhu kontroler motor BLDC pada purwarupa kendaraan listrik - Leo Arinando; Fatkhur Rohman (TURBO [Tulisan Riset Berbasis Online], 2020)
Electric vehicles are currently being developed with the concept of saving energy and  environmentally responsible. Electric vehicles use electric motors as the main driving motor. The electric motor which is currently increasingly used is the Brushless Direct Current (BLDC) motor. The BLDC motor controller is more expensive than the price of the BLDC motor itself. The BLDC motor controller has a working temperature range when working. The purpose of this study was to analyze the effect of variations in load values and the speed of electric vehicles on the temperature of the BLDC motor controller. This research was conducted by the experimental method by giving a treatment, then evaluating the effect caused on an object of research. The results showed that there was an influence of load value variations on the BLDC motor controller temperature. Values that look significant are at speeds of 0.5 m/sec and 2.5 m/sec starting from 3 kg to 5 kg. There is no influence on the variation of speed values on the temperature of the BLDC motor controller. The temperature value is stable at 2 kg and 3 kg loads with speed variations from 0.5 m/sec to 2.5 m/sec. Simultaneously variations in load and speed values affect the temperature of the BLDC motor controller by 57.7% with the lowest temperature value at 0.5 m/s and a load of 1 kg with a temperature of 33.34℃ and the highest temperature value at a speed of 2.5 m/sec and a load of 5 kg with a temperature of 37.58℃.Keywords: Electric vehicles, controllers, BLDC motors, temperature.